Genomewide Association Study of Acute Anterior Uveitis Identifies New Susceptibility Loci - Huang, Xiu-Feng; Li, Zhixiu; De Guzman, Erika; Robinson, Philip; Gensler, Lianne; Ward, Michael M.; Rahbar, Mohammad Hossein; Lee, MinJae; Weisman, Michael H.; Macfarlane, Gary J.; Jones, Gareth T.; Klingberg, Eva; et al. (Investigative ophthalmology & visual science, 2020)
Acute anterior uveitis (AAU) is a common intraocular inflammatory disease. AAU occurs in 30% to 50% of patients with ankylosing spondylitis (AS), and both conditions are strongly associated with human leukocyte antigen (HLA)-B27, implying a shared etiology. This study aims to apply genomewide association study (GWAS) to characterize the genetic associations of AAU and their relationship to the genetics of AS. We undertook the GWAS analyses in 2752 patients with AS with AAU (cases) and 3836 patients with AS without AAU (controls). There were 7,436,415 single-nucleotide polymorphisms (SNPs) available after SNP microarray genotyping, imputation, and quality-control filtering. We identified one locus associated with AAU at genomewide significance: rs9378248 (P = 2.69 × 10-8, odds ratio [OR] = 0.78), lying close to HLA-B. Suggestive association was observed at 11 additional loci, including previously reported AS loci ERAP1 (rs27529, P = 2.19 × 10-7, OR = 1.22) and NOS2 (rs2274894, P = 8.22 × 10-7, OR = 0.83). Multiple novel suggestive associations were also identified, including MERTK (rs10171979, P = 2.56 × 10-6, OR = 1.20), KIFAP3 (rs508063, P = 5.64 × 10-7, OR = 1.20), CLCN7 (rs67412457, P = 1.33 × 10-6, OR = 1.25), ACAA2 (rs9947182, P = 9.70 × 10-7, OR = 1.37), and 5 intergenic loci. The SNP-based heritability is approximately 0.5 for AS alone, and is much higher (approximately 0.7) for AS with AAU. Consistent with the high heritability, a genomewide polygenic risk score shows strong power in identifying individuals at high risk of either AS with AAU or AS alone. We report here the first GWAS for AAU and identify new susceptibility loci. Our findings confirm the strong overlap in etiopathogenesis of AAU with AS, and also provide new insights into the genetic basis of AAU.